Italian Legal Euthanasia: Unconstitutionality of the Referendum and Analysis of the “Italian” Problem - Marrone, Maricla; Berardi, Pietro; Solarino, Biagio; Ferorelli, Davide; Corradi, Serena; Silvestre, Maria; De Luca, Benedetta Pia; Stellacci, Alessandra; Dell'Erba, Alessandro (Frontiers in Sociology, 2022)
The term “euthanasia” refers to medical interventions that involve the direct administration of a lethal drug to the patient who requests it and meets certain requirements. Currently in Italy euthanasia constitutes a crime and falls within the hypotheses foreseen and punished by Article 579 (Murder of consenting person) or by article 580 (Instigation or aid to suicide) of the penal code. On the contrary, medically assisted suicide in some cases and the suspension of treatment constitute an inviolable right pursuant to art. Thirty two of the Constitution and Law 219/2017. Thanks to the sentence 242/2019 of the Constitutional Court, in Italy it is instead possible to request medically assisted suicide, that is, the indirect help of a doctor to die. There are four conditions required: whoever requests it must be fully capable of understanding and willing, must have an irreversible pathology that is the bearer of severe physical or mental disease, and must survive thanks to life-saving treatments. The Italian referendum “Free until the end” aims to introduce legal euthanasia through the partial repeal of art. 579 c.p. which punishes the murder of the consenting party. The authors analyze the reasons for the referendum in the light of the Italian and European scenario, analyzing the first Italian case of assisted suicide immediately after the referendum which inevitably becomes a starting point for ethical and medico-legal reflection on the issue. On 02.15.2022 the Italian Constitutional Court declared the Referendum on Legal Euthanasia inadmissible.